A narrative review of Men's Sheds literature: reducing social isolation and promoting men's health and well-being - Wilson, N.; Cordier, Reinie (Wiley-Blackwell Publishing Ltd., 2013)
Men’s Sheds are community-based organisations that typically provide aspace for older men to participate in meaningful occupation such aswoodwork. Men’s Sheds are considered an exemplar for the promotionof men’s health and well-being by health and social policy-makers. Theobjective of this literature review was to determine the state of thescience about the potential for Men’s Sheds to promote male health andwell-being. Between October 2011 and February 2012, we conductedsearches of databases, the grey literature and manual searches ofwebsites and reference lists. In total, we found 5 reports and 19 articlesabout Men’s Sheds. The majority of the literature has emanated fromAustralian academics and is about older men’s learning in communitycontexts. There is a limited body of research literature about Men’sSheds; the literature consists of either descriptive surveys or smallqualitative studies. The range of variables that might contribute towardsbest practice in Men’s Sheds has not yet been adequately conceptualised,measured, tested or understood. Future research should be focussed onthe health and well-being benefits of Men’s Sheds; it needs to incorporatesocial determinants of health and well-being within the studydesigns to enable comparison against other health promotion research.Without this research focus, there is a danger that the potential healthand well-being benefits of Men’s Sheds as supportive and sociallyinclusive environments for health will not be incorporated into futuremale health policy and practice.